THE VIEWS OF EASTERN AND WESTERN THINKERS ON THE FORMATION OF SPEAKING ART. - Shotemirov Sanjar Xolmo‘min o‘g‘li (Scholar Express Journal, 2023)
The purpose of this article is to research the process of formation of public speaking skills in young students based on a psychological approach. For this, we need to introduce you to the main rules that must be followed when developing the content of speech , and draw your attention to the psychological obstacles that occur in this process. We also tried to explain in detail how to create and improve public speaking and how to overcome psychological obstacles in this process.
Keywords: Elocution; speaking; skill; conversation